2021
DOI: 10.1126/sciadv.abf0669
|View full text |Cite
|
Sign up to set email alerts
|

Molecular insights on confined water in the nanochannels of self-assembled ionic liquid crystal

Abstract: Self-assembled ionic liquid crystals can transport water and ions via the periodic nanochannels, and these materials are promising candidates as water treatment membranes. Molecular insights on the water transport process are, however, less investigated because of computational difficulties of ionic soft matters and the self-assembly. Here we report specific behavior of water molecules in the nanochannels by using the self-consistent modeling combining density functional theory and molecular dynamics and the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 71 publications
1
58
0
Order By: Relevance
“…Recently, some of the present authors have found that it is possible to distinguish the characteristics of water molecules inside the condensed organic–water complex by employing molecular dynamics (MD) simulations. 33 Therefore, to quantitatively evaluate the relative contributions of the abovementioned three possibilities, information derived from MD simulations is considered to be most helpful. Theoretical analyses on this point will be deferred to later studies.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, some of the present authors have found that it is possible to distinguish the characteristics of water molecules inside the condensed organic–water complex by employing molecular dynamics (MD) simulations. 33 Therefore, to quantitatively evaluate the relative contributions of the abovementioned three possibilities, information derived from MD simulations is considered to be most helpful. Theoretical analyses on this point will be deferred to later studies.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of polymerization on the hydration state is quite interesting. It is also expected that the present concept of the pseudo-temperature-change deserve a variety of macromolecular or polymer systems, for which roles of water have been widely paid attention recently. ,, …”
Section: Discussionmentioning
confidence: 99%
“…It is also expected that the present concept of the pseudo-temperature-change deserve a variety of macromolecular or polymer systems, for which roles of water have been widely paid attention recently. [36][37][38]59,60 ■ ASSOCIATED CONTENT * sı Supporting Information…”
Section: ■ Conclusionmentioning
confidence: 99%
“…6d and e). 33 Thereby, ne-tuning of the phase transition of the SRPILs is quite an effective strategy to improve the adsorption and separation of CO 2 /C 2 H 4 . 25 Moreover, the adsorptive capacity of CO 2 and C 2 H 4 increases with increasing loading of ZIF-8 in the SRPILs, which benets from the introduction of the more permanent porosity of ZIF-8.…”
Section: Co 2 /C 2 H 4 Adsorption and Separation Performances Of The ...mentioning
confidence: 99%